THE ROLE OF TRANSFORMATIVE LEADERSHIP IN MADRASAH QUALITY DEVELOPMENT AT MIN 1 PEMALANG - Saparudin, Eko; Senowarsito, Senowarsito; Maryanto, Maryanto (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Transformative leadership is a key element in strengthening the quality of madrasah education, making it adaptive to the dynamics of 21st-century education. This study aims to analyze in depth the transformative leadership of madrasah principals in building excellent madrasahs at MIN 1 Pemalang. This study provides an empirical mapping of the five dimensions of transformative leadership in the madrasah environment and provides contextual evidence. This research topic has not been widely studied or reported on in previous research. The study uses a qualitative case study design. This study involved madrasah principals, teachers, and educational staff as informants. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis was conducted interactively through data reduction, presentation, and verification, with triangulation of sources and methods to ensure the validity of the findings. The results showed that the madrasah principal successfully implemented five dimensions of transformative leadership comprehensively, including participatory strategic visioning, motivational moral exemplification, adaptive open communication, teacher professionalism development through reflective mentoring, and human resource empowerment based on potential and collaboration. These five dimensions contribute to the formation of a collaborative, innovative, and quality-oriented work culture. These findings can certainly strengthen teacher professionalism and enhance the competitiveness of madrasahs as superior, character-building Islamic educational institutions.